Improvement of Institutional Mechanisms of Development of Service Enterprises (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The socio-economic significance, content, and essence of the development of the service sector, structural transformations implemented in the industry, types, and characteristics of services according to classification criteria, as well as the features and principles of effective development of the service sector are examined in the article.